Short and long term degradation behaviour of Mg–1Ca magnesium alloys and protective coatings based on plasma‐chemical oxidation and biodegradable polymer coating in synthetic body fluid. Issue 8 (16th May 2012) - Rosemann, P.; Schmidt, J.; Heyn, A.
Abstract: The main problem limiting the application of magnesium alloys as biodegradable implant material is its high degradation rate. In order to slow down the corrosion rate an extrusion process and specific coating systems based on plasma‐chemical oxidation (PCO) and organic dip coating with poly(L ‐lactid‐co‐caprolacton) (PLLC) were applied on Mg–1Ca magnesium alloy. The additional PLLC coating is used to delay the start of substrate corrosion, while the purpose of the PCO coating is to decrease the substrate corrosion rate. The corrosion behaviour was investigated in synthetic body fluid (SBF) through measurement of the hydrogen evolution rate in long term tests and polarisation and electrochemical noise measurements in short term tests. The results showed significant differences between the cast and extruded alloys and a decrease of the corrosion rate due to corrosion product formation. The combination of both coating systems resulted in a significant delay of metal substrate corrosion and all coating systems showed good correlation between short and long term tests. The combination of the three investigation methods provides the possibility to gain more information about the degradation behaviour and break down of protective coatings.